THE ROLE OF BAZNAS NORTH SUMATRA PROVINCE IN ENCOURAGING SUSTAINABLE DEVELOPMENT GOALS (SDGS) THROUGH SOCIAL IMPACT-BASED ZAKAT ACCOUNTING - Lubis, Muhammad Alpansyah; Nasution, Yenni Samri Juliati; Nasution, Muhammad Lathief Ilhamy (Pena Cendekia Insani, 2025)
Achieving the Sustainable Development Goals (SDGs) requires cross-sector collaboration, including in zakat management. BAZNAS North Sumatra Province is strategically positioned to support the achievement of SDGs 1, 4, and 8 through a productive zakat program. However, reporting practices that still emphasize financial output aspects make measuring social impact less than optimal. Examining the role of BAZNAS North Sumatra Province in encouraging the achievement of SDGs through the implementation of social impact-based zakat accounting, with a focus on the effectiveness of business capital assistance programs and assistance in completing student final assignments. This study uses a descriptive-explanatory design with a mixed methods approach. Qualitative data were collected through interviews, observations, and document reviews, while quantitative data were analyzed using the Social Return on Investment (SROI) framework on 54 beneficiary respondents. The business capital assistance program increased the average income of mustahik by 20.58% with an SROI ratio of 1:2.83, and encouraged independence and self-confidence. Meanwhile, the thesis completion assistance program accelerated graduation, enabled 100% of its recipients to obtain employment, and achieved an SROI ratio of 1:7.87. Both programs significantly contribute to the achievement of SDGs 1, 4, and 8. This research combines the application of social impact-based zakat accounting with quantitative SROI measurements at the provincial BAZNAS level. The results provide empirical evidence of zakat's role in supporting the SDGs and offer an outcome-based evaluation model with potential adaptation in other regions.